2004
DOI: 10.1074/jbc.m311427200
|View full text |Cite
|
Sign up to set email alerts
|

RhoA/ROCK Signaling Suppresses Hypertrophic Chondrocyte Differentiation

Abstract: Coordinated proliferation and differentiation of growth plate chondrocytes is required for normal growth and development of the endochondral skeleton, but little is known about the intracellular signal transduction pathways regulating these processes. We have investigated the roles of the GTPase RhoA and its effector kinases ROCK1/2 in hypertrophic chondrocyte differentiation. RhoA, ROCK1, and ROCK2 are expressed throughout chondrogenic differentiation. RhoA overexpression in chondrogenic ATDC5 cells results i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

9
118
3

Year Published

2004
2004
2015
2015

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 118 publications
(132 citation statements)
references
References 102 publications
9
118
3
Order By: Relevance
“…Overexpression of RhoA inhibits Sox9 expression, stimulates cyclin D1 activation, and suppresses hypertrophy in ATDC5 cells. [16,17,34] However, in micromass limb bud cells, RhoA induces Sox9 expression and early chondrocyte differentiation. We do not see an increase in RhoA activity with maturation.…”
Section: Rho Gtpase Activity With Maturationmentioning
confidence: 99%
See 2 more Smart Citations
“…Overexpression of RhoA inhibits Sox9 expression, stimulates cyclin D1 activation, and suppresses hypertrophy in ATDC5 cells. [16,17,34] However, in micromass limb bud cells, RhoA induces Sox9 expression and early chondrocyte differentiation. We do not see an increase in RhoA activity with maturation.…”
Section: Rho Gtpase Activity With Maturationmentioning
confidence: 99%
“…In gain-of-function experiments using the chondrogenic cell line ATDC5, RhoA over-expression was found to induce actin filament organization and stress fibers, to increase proliferation and proteoglycan production, and to suppress maturation and hypertrophy. [16,17] Conversely, overexpression of Rac-1 and Cdc42 in ATDC5 cells induces collagen type X expression, alkaline phosphatase activity, and matrix mineralization, which are associated with mature chondrocytes. [18] A recent study has indicated that genetic ablation of Rac-1 in developing cartilage leads to growth retardation with irregular growth plate organization, suppression of chondrocyte proliferation and a decreased area of collagen type X expression, indicating a delay in chondrocyte differentiation.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, the connections between extracellular signals and intracellular mediators in the control of cyclin D1 expression is poorly understood in most cases. While protein kinase A, RhoA, and the transcription factor CREB have been shown to be required for induction of cyclin D1 transcription by PTHrP (Beier et al, 2001;Ionescu et al, 2001;Beier and LuValle, 2002;Wang et al, 2004), and ATF-2 has been implicated in activation of the cyclin D1 promoter by TGFb (Beier et al, 2001), much less is known about the signaling molecules and transcription factors utilized by the other pathways listed above. Moreover, the regulation of cyclin D2 and D3 genes by these (or other) pathways has not been investigated.…”
Section: Control Of Cell-cycle Gene Expression In Chondrocytesmentioning
confidence: 99%
“…However, Wnt5a deficiency also results in reduced cyclin D1 expression, but this effect might be secondary to a loss of Indian hedgehog expression in the bones of Wnt5a-deficient mice . Similarly, intracellular signaling molecules such as integrin-linked kinase (Grashoff et al, 2003;Terpstra et al, 2003), the small GTPase RhoA (Wang et al, 2004) and the transcription factor c-Fos (Sunters et al, 1998) also stimulate cyclin D1 expression in cartilage.…”
Section: Control Of Cell-cycle Gene Expression In Chondrocytesmentioning
confidence: 99%